(untitled) (American Journal of Energy and Natural Resources, 2022)
Energy audit is one lever to reduce carbon emissions of an organization (industrial site, residential building etc.;). This paper explores the energy audit savings tendance, barriers, challenges, and opportunities through an extensive review of the literature. Different variant of the methodology can be found in the literature and one aim of this research is to make a synthesis (from the most relevant variant). Energy audit can be adapted to the size and context of the organization thanks to the different levels of audits. Different cases studies are also included in this article that highlights the benefits of the energy audit. Other aspects are studied such as tools to use during audit and competencies and experience of auditors. Several barriers should be removed progressively to add more benefits to this sustainable lever. A list of opportunities has been identified and should be subject to further research.